Patients' Experiences of Shared Decision Making in Primary Care Practices in the United Kingdom. (January 2013) - Fullwood, Catherine; Kennedy, Anne; Rogers, Anne; Eden, Martin; Gardner, Caroline; Protheroe, Joanne; Reeves, David
Background . Shared decision making (SDM) and patient self-management support are key components of US and UK policy for chronic disease management, whereby SDM is seen as enhancing physician-patient negotiation around self-management. The WISE trial is implementing training in self-management support for primary care physicians in one UK region. This article describes preintervention levels of patient-reported SDM and explores how this varies with patient and practice characteristics.Methods . We analyzed baseline data from a cluster randomized controlled trial for 2965 patients with diabetes, chronic obstructive pulmonary disease, and irritable bowel syndrome (IBS) from 29 family practices. Patient-level measures included self-report of chronic conditions, SDM (Health Care Climate Questionnaire [HCCQ]), health status, and demographic characteristics. Area and practice characteristics included chronic disease workload and socioeconomic deprivation.Results . The mean SDM score was 75 (out of 100), but the range was wide. The mean score was lower for IBS patients but did not vary with other disease conditions. Younger patients and those with poorer health status reported lower degrees of SDM. No associations were found with practice characteristics.Limitations . The study was restricted to one socioeconomically deprived region, and hence results may not be nationally representative of the United Kingdom. Ceiling effects on SDM scores may limit the utility of the HCCQ.Conclusions . Lower ratings from some patient groups may reflect differences in expectations rather than differences in physician behavior. Overall levels of SDM were high, and no patient or practice characteristic represented a serious barrier to SDM. However, we cannot say to what extent SDM in this chronic population addressed self-management issues rather than clinical care. More nuanced measures of SDM are required that distinguish between different forms of care.